Efficacy and safety of dietary polyphenol supplementation in the treatment of non-alcoholic fatty liver disease: A systematic review and meta-analysis - Yang, Kailin; Chen, Junpeng; Zhang, Tianqing; Yuan, Xiao; Ge, Anqi; Wang, Shanshan; Xu, Hao; Zeng, Liuting; Ge, Jinwen (Frontiers in Immunology, 2022)
Background Dietary polyphenol treatment of non-alcoholic fatty liver disease (NAFLD) is a novel direction, and the existing clinical studies have little effective evidence for its therapeutic effect, and some studies have inconsistent results. The effectiveness of dietary polyphenols in the treatment of NAFLD is still controversial. The aim of this study was to evaluate the therapeutic efficacy of oral dietary polyphenols in patients with NAFLD. Methods The literature (both Chinese and English) published before 30 April 2022 in PubMed, Cochrane, Medline, CNKI, and other databases on the treatment of NAFLD with dietary polyphenols was searched. Manual screening, quality assessment, and data extraction of search results were conducted strictly according to the inclusion and exclusion criteria. RevMan 5.3 software was used to perform the meta-analysis. Results The RCTs included in this study involved dietary supplementation with eight polyphenols (curcumin, resveratrol, naringenin, anthocyanin, hesperidin, catechin, silymarin, and genistein) and 2,173 participants. This systematic review and meta-analysis found that 1) curcumin may decrease body mass index (BMI), Aspartate aminotransferase (AST), Alanine aminotransferase (ALT), Triglycerides (TG) total cholesterol (TC), and Homeostasis Model Assessment-Insulin Resistance (HOMA-IR) compared to placebo; and curcumin does not increase the occurrence of adverse events. 2) Although the meta-analysis results of all randomized controlled trials (RCTs) did not reveal significant positive changes, individual RCTs showed meaningful results. 3) Naringenin significantly decreased the percentage of NAFLD grade, TG, TC, and low-density lipoprotein cholesterol (LDL-C) and increased high-density lipoprotein cholesterol (HDL-C) but had no significant effect on AST and ALT, and it is a safe supplementation. 4) Only one team presents a protocol about anthocyanin (from Cornus mas L. fruit extract) in the treatment of NAFLD. 5) Hesperidin may decrease BMI, AST, ALT, TG, TC, HOMA-IR, and so on. 6) Catechin may decrease BMI, HOMA-IR, and TG level, and it was well tolerated by the patients. 7) Silymarin was effective in improving ALT and AST and reducing hepatic fat accumulation and liver stiffness in NAFLD patients. Conclusion Based on current evidence, curcumin can reduce BMI, TG, TC, liver enzymes, and insulin resistance; catechin can reduce BMI, insulin resistance, and TG effectively; silymarin can reduce liver enzymes. For resveratrol, naringenin, anthocyanin, hesperidin, and catechin, more RCTs are needed to further evaluate their efficacy and safety.